Desa Membangun UMKM: Pendampingan UMKM berbasis Village-Driven Development dalam Penguatan Ekonomi Warga Di Desa Gogodeso Kecamatan Kanigoro Kabupaten Blitar - Luhung Achmad Perguna; Imamul Huda Al Siddiq; Irawan (Asosiasi Dosen Pengembang Masyarajat (ADPEMAS) Forum Komunikasi Dosen Peneliti, 2019)
Village dignity is evident from the efforts of the village to mobilize all of its resources, including in strengthening the Micro Small Medium Enterprise (MSMEs) sector. Strengthening MSMEs becomes important as an economic asset of the village, while at the same time reducing rural and urban inequality.This effort continues to be carried out and endeavored by the village of Gogodeso, Kanigoro sub-district, Blitar district. Since because they are aware of its great potential, unfortunately it has not been optimized. The vision of building a village changes. With the facilitation from team, it is optimized by first analyzing the potential situation of MSMEs through the Participatory Rural Appraisal approach based on Village-Driven Development, which means that it requires the active involvement of all village stakeholders. Followed by the alignment of vision and mission through the Building Village Workshop and finally through assistance in marketing through packaging branding as part of the problems of SMEs so far. These three steps are part of an effort to turn Gogodesa village into the MSME Goddess (MSME-based Tourism Village). The result is that the community who initially wanted to build an agriculture-based village changed and agreed to build an MSME-based village.